2010 Sixth International Conference on Intelligent Information Hiding and Multimedia Signal Processing 2010
DOI: 10.1109/iihmsp.2010.85
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Hand or Wrist Vein Images for Biometric Authentication Using Low-Cost Devices

Abstract: Biometric recognition is becoming more and more important owing to the need for authentication in several fields like security or convenience applications. In this paper, a new imaging capturing technique based on near-infrared illumination [1] to acquire wrist vein pattern images for biometric purposes is analysed. Experiments and tests involving data acquisition in different illumination conditions are described using a population of 30 test subjects. Comparison and analysis of the data collected with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 3 publications
0
22
0
1
Order By: Relevance
“…The third database used for the experiment is referred to as UC3M [10]. It was collected in 2010 in the University Carlos III of Madrid.…”
Section: Databasesmentioning
confidence: 99%
“…The third database used for the experiment is referred to as UC3M [10]. It was collected in 2010 in the University Carlos III of Madrid.…”
Section: Databasesmentioning
confidence: 99%
“…The patterns are commonly extracted from images of the palm, the back of the hand or fingers as seen in figure 1, also the wrist area can be used [8]. Yanagawa et al showed that the diversity of finger vein patterns among different persons is competitive to iris-based systems [9].…”
Section: Vein Pattern Recognitionmentioning
confidence: 99%
“…Pascual et al [12] built a vein recognition system where quality of the produced samples were measured through objective measurements such as contrast, variance and light distribution between vein and skin area. Several studies have demonstrated the correlation between quality and influencing factors of different nature and with different degrees of influence.…”
Section: Related Workmentioning
confidence: 99%